Ilex paraguariensis extract as an alternative to pain medications - Nowacki Luciana C.; Stechman-Neto José; Schiefer Elberth M.; Santos Andressa F.; Stinghen Andréa E. M.; Sassaki Guilherme L.; De Souza Lauro M.; Cristoff Killian E.; De Souza Wesley M. (Acta Pharmaceutica)
Pain is a common and distressing symptom of many diseases and its clinical treatment generally involves analgesics and anti-inflammatory drugs. This study evaluated the toxicity of Ilex paraguariensis A. St.-Hil. (Aquifoliaceae) aqueous extract (leaves, petioles and branches) and its performance in a nociceptive response. Hepatotoxicity, psycho-stimulant test and evaluation of enzyme markers for liver damage were also tested. Chromatographic analysis by UPLC-MS demonstrated a series of isomeric monocaffeoylquinic acids, isomers of dicaffeoylquinic acid, flavonol glycosides, and saponins. Phase I and II of nociception were obtained for meloxicam, dexamethasone and aqueous Ilex paraguariensis extract. Ilex paraguariensis extract concentration was negatively correlated (R = –0.887) with alanine aminotransferase (p < 0.05) in acetaminophen-induced hepatotoxicity test, indicating hepatoprotective activity of this extract. Ilex paraguariensis extract also presented analgesic properties equivalent to drugs that already have proven efficacy. Notably, the administration of multiple doses of Ilex paraguariensis extract was considered safe from the therapeutic point of view.